2021
DOI: 10.1126/sciimmunol.abf0125
|View full text |Cite
|
Sign up to set email alerts
|

A fetal wave of human type 3 effector γδ cells with restricted TCR diversity persists into adulthood

Abstract: Accumulating evidence suggests that the mouse embryonic thymus produces distinct waves of innate effector γδ T cells. However, it is unclear whether this process occurs similarly in humans and whether it comprises a dedicated subset of innate-like type 3 effector γδ T cells. Here, we present a protocol for high-throughput sequencing of TRG and TRD pairs that comprise the clonal γδTCR. In combination with single-cell RNA sequencing, multiparameter flow cytometry, and TCR sequencing, we reveal a high heterogenei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 80 publications
11
88
0
Order By: Relevance
“…For example, it was shown that a subpopulation of CD28 + Vγ9Vδ2 cells produce IL-17, are positive for CD27 and CCR6 and express type-3 signature genes such as RORC and IL23R [ 56 ]. Notably, the recent identification of γδT17 Vδ2 cells in human embryonic thymus also suggests a potential pre-programing mechanism similar to mice [ 57 ].…”
Section: Functional γδ T-cell Subsets In Mice and Humansmentioning
confidence: 99%
“…For example, it was shown that a subpopulation of CD28 + Vγ9Vδ2 cells produce IL-17, are positive for CD27 and CCR6 and express type-3 signature genes such as RORC and IL23R [ 56 ]. Notably, the recent identification of γδT17 Vδ2 cells in human embryonic thymus also suggests a potential pre-programing mechanism similar to mice [ 57 ].…”
Section: Functional γδ T-cell Subsets In Mice and Humansmentioning
confidence: 99%
“…In this sense, γδ T cells were subjected to flow cytometric analysis with antibodies specific for Vδ1 + , Vδ2 + , Vδ3 + and Vγ9 + T cell receptors (TCRs). At the same time, antibodies against CD27, CD45RA, CCR7, and CD127 were used to identify naïve and central memory cells; CCR4 for type 2-immunity γδ T cells; CCR6 and CD161 for innate type 3-immunity γδ T cells; and CD94, CD16, and PD1 for cytotoxic type 1 effector γδ T cells ( 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…One subpopulation of T lymphocytes, gd T cells, could be essential to early neonatal and childhood protection. They start to develop during early fetal development, show a high functionality at birth and fast expansion upon microbial encounters (4)(5)(6)(7)(8)(9). Murine and human gd T cells are often grouped based on their surface gd T cell receptor and functionality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations